TINJAUAN ANALITIS DAN EKSPERIMENTAL SQUARE TRUSS BAMBU DENGAN BEBAN AKSIAL - , TEGUH ANANTO UTOMO, Prof. Ir. Morisco, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Bamboo is a very potential material, because it can grow almost everywhere and is relatively easy to obtain. The use of bamboo as a raw construction material has been widely applied, either by its safe structural analysis, or by empirical experience that has been passed down through generations, such as those used for the beams, columns and the frames. Nowadays, bamboo was developed to be used in square truss structure, which could be used as main structure towards either a beam or column in a bamboo house construction. But, a few questions emerged, what if bamboo is used in a column post, how the lenght of bamboo square truss affects the maximum axial load, and what is the effect of mortar addition towards the strength and weight of the structure. In this research, the bamboo square truss column was made of wulung bamboo (Gigantochloa atroviolacea) with Â±8 cm in diameter as the main column stem and ornamental bamboo (Dracaena Surculosa) with Â±3 cm in diameter as a diagonal stem. The stems were assembled into a 3D square truss structure, with 30 cm in width and 30 cm in height. The bamboo square truss column model was made in two types, one model with mortar and the other model without mortar. The square truss variation without mortar is as follows: ST-30/30-L Model =300 cm, ST-30/30- L Model=350 cm and ST-30/30-L Model =400 cm. The other variation was the addition of mortar to create a square truss with mortar, which is the ST-30/30(M)-L Model=350 cm. These models axial loads were tested using hydraulic jack, load cell, LVDT and data logger tools, the magnitude of the axial load was predicted beforehand by using Euller Equation and SAP2000 analysis. The result of the test, the Pmaks, was then compared with the numerical analysis (SAP 2000) and Euller analysis results. According to the test result, Euller, and SAP2000 test, the Pmaks for each model without mortar was as follows: (1) ST-30/30-L Model=300 result was 55,33 kN